2016
DOI: 10.1007/s10854-016-5073-5
|View full text |Cite
|
Sign up to set email alerts
|

A multisource energy harvesting utilizing highly efficient ferroelectric PMN-PT single crystal

Abstract: A multi-source Energy Harvester employing simultaneously piezoelectric and pyroelectric effects in lead magnesium niobate-lead titanate (PMN-PT) single crystal is demonstrated. The article presents a study of PMN-PT with (67:33) composition single crystal grown in our laboratory via a vertical gradient freeze method with no flux. The performances of the piezoelectric and pyroelectric energy harvester using unimorphs were evaluated via modeling and experiments. The theoretical study was implemented based on sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…From Figure 5, it can be observed that maximum output voltage (occurring at resonance) increases slightly with the increase in resistive load value. Figure 6 shows the variation calculated power as a function of frequency and these results agree with the available literature [39][40]. Figure 7 shows the voltage measured across the load resistor and power dissipated by it at resonance frequency extracted from Figure 5 at the peak of the curve.…”
Section: Example Of Measurement Resultssupporting
confidence: 83%
“…From Figure 5, it can be observed that maximum output voltage (occurring at resonance) increases slightly with the increase in resistive load value. Figure 6 shows the variation calculated power as a function of frequency and these results agree with the available literature [39][40]. Figure 7 shows the voltage measured across the load resistor and power dissipated by it at resonance frequency extracted from Figure 5 at the peak of the curve.…”
Section: Example Of Measurement Resultssupporting
confidence: 83%
“…A cantilever beam with a tip mass was developed with the single crystal PMN-PT with (67:33) composition as piezoelectric material, grown via a vertical gradient freeze method. The system was excited under an acceleration of 1g at a resonance frequency of 50 Hz and the maximum power obtained was 5 nW/g 2 for an optimum resistive load of 2 MΩ, with a cantilever of approximately 0.300 cm 3 and 6.03 g. The system was tested to recharge a CMOS lithium battery with nominal operating voltage of 3.0 V, and at the resonance frequency and optimum resistance the output voltage increased up to a constant value of 2.88 V, which corresponds to approximately 92% of the full charge of the rechargeable battery [137]. A comparison study of the energy harvesting efficiency between PMN-PT, PZN-PT and the ceramic PZT cantilever beams was performed, and both single crystals based systems showed higher performance than the ones fabricated from PZT.…”
Section: Piezoelectric Energy Harvesting Based On Single Crystalsmentioning
confidence: 99%
“…Ferroelectrics have been used to improve the output power in PEHs [12,[43][44][45][46], as well as pyroelectric energy harvesters and even photovoltaics [47][48][49][50][51]. With the advance of nano-technology, ferroelectrics are also used in emerging energy harvesting mechanisms employing triboelectricity.…”
Section: Introductionmentioning
confidence: 99%